2022
DOI: 10.1126/sciadv.abo6566
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR interference interrogation of COPD GWAS genes reveals the functional significance of desmoplakin in iPSC-derived alveolar epithelial cells

Abstract: Genome-wide association studies (GWAS) have identified dozens of loci associated with chronic obstructive pulmonary disease (COPD) susceptibility; however, the function of associated genes in the cell type(s) affected in disease remains poorly understood, partly due to a lack of cell models that recapitulate human alveolar biology. Here, we apply CRISPR interference to interrogate the function of nine genes implicated in COPD by GWAS in induced pluripotent stem cell–derived type 2 alveolar epithelial cells (iA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…In addition, as mentioned above, the cellular distribution of HHIP differs between mice and humans; abundant expression of HHIP in human AT2 cells might dictate alternative outcomes in response to injury in humans. We recently applied induced pluripotent stem cell-derived AT2 (iAT2) cells to interrogate the function of COPD GWAS genes, and found that HHIP expression regulated SFTPC expression in iAT2 cells but did not alter other aspects of AT2 cells (such as proliferation or differentiation capacity) [ 83 ]. Future studies, potentially employing iAT2 cells or precision-cut lung slices, elucidating responses to injury ( e.g.…”
Section: Hhipmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, as mentioned above, the cellular distribution of HHIP differs between mice and humans; abundant expression of HHIP in human AT2 cells might dictate alternative outcomes in response to injury in humans. We recently applied induced pluripotent stem cell-derived AT2 (iAT2) cells to interrogate the function of COPD GWAS genes, and found that HHIP expression regulated SFTPC expression in iAT2 cells but did not alter other aspects of AT2 cells (such as proliferation or differentiation capacity) [ 83 ]. Future studies, potentially employing iAT2 cells or precision-cut lung slices, elucidating responses to injury ( e.g.…”
Section: Hhipmentioning
confidence: 99%
“…Mechanistically, the absence of Fam13a in mice is protective through increased β-catenin signalling and subsequent increased cellular proliferation [ 84 ] and decreased fatty acid oxidation and associated cellular stress [ 96 ], suggesting that elevated FAM13A expression in COPD patients might impede lung epithelial repair in response to injury. To explore the function of FAM13A in human AT2 cells, we recently applied CRISPR interference to knock down full-length FAM13A in iAT2 cells [ 83 ]. Surprisingly, in contrast to the in vivo mouse studies, loss of FAM13A slowed iAT2 proliferation [ 83 ], potentially on the basis of differences in FAM13A isoforms expressed in mice versus humans.…”
Section: Fam13amentioning
confidence: 99%
See 3 more Smart Citations